Ecofeminism and Sustainable Development Goals (SDG) Agenda 2030 (International Journal of Innovative Research in Engineering & Management, 2021)
Development is a contentious term that is still changing inside that  worldwide discussion, towards which gendered studies makes a  significant contribution. However, because there is no consensus  upon the loose interpretation of advancement, including the  gendered component around between is also controversial. The  objective of this study is to investigate the impact of development  policies upon this experiences of women via the lens paradigm  reconstructive anthropological ecofeminism. As a result, our  research is predicated on the idea that the ecosystem as well as  women are inextricably linked in terms of government  development. As a result of the constructivist theory's avoidance  of essentials, women are pushed to behave as historical and  psychological agents simply because that is in their essential, but  only because the masculine economic society severely limits as  well as limits their options. The influence of development  methods on women's relationships with both the environment as  well as modernization processes will be examined. This study provides newer insightfulness within the effects regarding development methods in the industries as well as companies,  food, as well as health on women's living situations. It will  emphasize how such behaviors exacerbate gender inequality,  food hardship, as well as infection risks. In this regard, donors as  well as actors must properly integrate fundamental elements not  only through their rules but also in their practices.
Keywords: Development; Ecofeminism; Ecofeminist; Education; Society; Women